1999
DOI: 10.1046/j.1439-0272.1999.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL-12, IL-10, PGE2, sIL-2R and sIL-6R in seminal plasma of fertile and infertile men

Abstract: The involvement of cytokines and other immunoregulatory factors in male infertility is still unclear. In the present study we compared the levels of IL-12, IL-10, PGE2, sIL-2R and sIL-6R in the seminal plasma (SP) of fertile and infertile men. Four groups were included: fertile donors (FERT), infertile men with azoospermia (AZOO), and infertile men with either oligoterato-asthenoazoospermia (OTA), or OTA with genital infection (OTA-INF). Cytokines and cytokine-soluble receptors in semen were evaluated by speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
(30 reference statements)
1
36
0
Order By: Relevance
“…[17][18][19]27,28 Some other SP cytokines, such as IL-10, had shown contradictory results among studies. Huleihel et al (1999) reported lower concentrations of IL-10 in infertile than fertile men, whereas Miller et al (2002) reported opposite results. 29,30 These conflicting results, together with the little current knowledge of the role played by SP cytokines on male reproductive performance, call for further studies.…”
Section: Discussionmentioning
confidence: 91%
“…[17][18][19]27,28 Some other SP cytokines, such as IL-10, had shown contradictory results among studies. Huleihel et al (1999) reported lower concentrations of IL-10 in infertile than fertile men, whereas Miller et al (2002) reported opposite results. 29,30 These conflicting results, together with the little current knowledge of the role played by SP cytokines on male reproductive performance, call for further studies.…”
Section: Discussionmentioning
confidence: 91%
“…In man, there has been extensive interest in seminal plasma cytokine profile, which has been characterised for IL-1a/b, IL-2, IL-4, IL-6, IL-8, IL-10, IL-11, IL-12, tumour necrosis factor (TNF)-a/b, IFN-a/g, TGF-b1, RANTES, CSF-1, G-CSF, macrophage-CSF, stem cell factor, monocyte chemotactic and activating factor, macrophage migration inhibitory factor and vascular endothelial growth factor as well as an array of their soluble receptors (Naz & Stanley 1995, Shimoya et al 1995, Frenette et al 1998, Fujisawa et al 1998a,b, Matalliotakis et al 1998a,b, 2002, Omu et al 1998, Huleihel et al 1999, Naz & Leslie 2000, Maegawa et al 2002, Gutsche et al 2003, Paulis et al 2003, Basu et al 2004. However, these studies have been limited in the array of cytokines investigated in individual patients, and their focus has principally been on the association of these inflammatory mediators with a variety of disorders resulting in male factor infertility and/or characterised by inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…It is still not clear whether some leukocyte contamination may have a positive influence on sperm function and which factors would change this effect. By observing molecular mechanisms of infertility it has been recently speculated that cytokines and their soluble receptors have a close relationship with male infertility and sperm function at particular steps of the reproduction process (Buch et al, 1994; Huleihel et al, 1996, 1999; Denison et al, 1999; Matalliotakis et al, 2000). Proinflammatory cytokines such as interleukin‐1 (IL‐1), interleukin‐6 (IL‐6), interleukin‐8 (IL‐8), and tumor necrosis factor‐α (TNF‐α) have been scrutinized in studies because the inflammation process is usually associated with their presence, and as a consequence, stimulates antioxidant feedback (Rajasekaran et al, 1995).…”
mentioning
confidence: 99%